SERUM FETUIN-A LEVELS IN PATIENTS WITH RHEUMATOID ARTHRITIS - E. V. Papichev; B. V. Zavodovsky; L. E. Sivordova; Yu. R. Akhverdyan; Yu. V. Polyakova (Научно-практическая ревматология, 2019)
Rheumatoid arthritis (RA) is the second most common rheumatic disease. In recent decades, there has been an active search for and study of biologically active substances involved in the pathogenesis of RA, which can serve as a starting point in designing new drugs for targeted therapy of this disease. The hepatokine fetuin-A (FA) is one of these substances.Objective: to investigate serum FA levels in patients with RA.Subjects and methods. The investigation enrolled 110 patients with RA. All the patients underwent the following set of studies: general blood test and determination of the serum levels of C-reactive protein (CRP), serum FA, rheumatoid factor, anti-cyclic citrullinated peptide (anti-CCP) antibodies, cartilage degradation products (CartiLaps), and urine creatinine. A control group consisted of 30 apparently healthy individuals whose serum FA level was determined in order to obtain reference values.Results and discussion. The normal FA level varied from 653.55 to 972.19 μg/ml. All the patients with RA were divided into two groups: 1) 23 patients with a low FA level (<653.55 μg/ml) and 2) 87 patients with a normal FA levels (≥653.55 μg/ml). The groups differed significantly in anti-CCP antibody concentrations, disease activity, radiological stages, functional classes, and the presence of complications. Patients with lower FA levels were noted to have increased CRP concentrations, erythrocyte sedimentation rate, and CartiLaps/urine creatinine ratio. The mean FA concentration was considerably and significantly lower in patients with higher DAS28 scores. Conclusion. Our investigation has revealed that there is a relationship between the levels of FA and the individual clinical manifestations of RA. The lower FA level is associated with higher disease activity and the aggressive phenotype of RA (the presence of anti-CCP antibodies, radiological stages III and IV, extra-articular manifestations and complications).